Types of interaction between the media and the audience - Makulbekov, А.T.; Malikova, A.M.; Rakimzhanova, S.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The ongoing transformations in modern society require rethinking from the angle of different theoretical and methodological approaches. The development of society and the world community cannot be imagined without the influence of mass communication and information. It is impossible to imagine the institute of mass media in modern society without an audience. For the successful functioning of the media, it is necessary to study information interaction, social characteristics of the audience and its feedback. The main tool for solving these problems will make it possible to better systematize the existing knowledge about the theory of interaction between the media and the audience, to trace its features in the upcoming professional practice and work in the media. Today, the process of systematization in these concepts can hardly be said to be logically complete. In theoretical publications, the mass media are interpreted ambiguously as a source of distributing information to the public. However, we believe that the mass media can also transmit a function as a way to create an individual.
Keywords: audience; media; interaction; culture; information